Energetska infrastruktura v luči prehoda v nizkoogljično družbo - quo vadis, Slovenija? - Drnovšek, Klemen (Podjetje in delo, 2021)
The authors of the article emphasise various aspects of current projects and plans for building energy infrastructure in the Republic of Slovenia (the RS) in light of the transition to a low-carbon society, hoping that strategic decisions will no longer be made in a hasty and ill-considered manner. Among other issues, the authors address the following: a question of increasing the share of renewable energy sources, problems related to the use of water and wind energy in the RS, as well as the question of involving non-governmental organisations and other stakeholders in the decision-making process from the perspective of public interest in the construction of energy facilities. In this context, they also compare the development of energy infrastructure and the status of non-governmental organisations in the RS with the development and the situation in Washington State, which is considered an evergreen state and a leading US state in the area of environmental protection and the transition to a low-carbon society. As the RS is a small country with a limited potential for more extensive developments, the discussion of energy needs should be laid out systemically - including the shift towards a reduction of the ever-increasing energy consumption (e.g. efficient energy use, more work from home, shorter work week, etc.).
Keywords: efficient energy use; energetska infrastruktura; energy infrastructure; hidroelektrarne; hydroelectric power plants; javni interes; low-carbon society; nevladne organizacije; nizkoogljična družba; non-governmental organisations; public interest; učinkovita raba energije; vetrne elektrarne; wind farms